The role of heart rate monitoring to assess workload during maintenance interval training in National Hunt racehorses - Williams, J.; Kenworthy, K.; Jones, T.; Marlin, D.; Tabor, G. (Journal of Veterinary Behavior Clinical Applications and Research, 2019)
Quantitative assessment of racehorse workload and fitness levels can be achieved through heart rate monitoring (HRM), an established reliable indicator of workload. Using HRM can aid trainers in formulating evidence-based training regimes and evaluating individual horses' progress during training. Despite this, HRM is not used consistently within racehorse training. This study aimed to evaluate how the maintenance workload of racehorses actively engaged in training and racing in the UK and varied across an interval-training regime (6 weeks). Ten thoroughbred racehorses (age: 9.1 ± 1.9 years) of mixed level (British Horseracing Authority Official Rating: 127.2 ± 7.95; career winnings: £34774.6 ± 21548.64) and experience in training (total races: 25 ± 12) were recruited for the study. Equinity Technology™ Ltd HRM systems collected weekly heart rate (HR) data for each horse during a maintenance interval training session (speed: 11 m/s) on a 3 furlong (0.38 m) all-weather gallop (sand, rubber, and wax mixture; 8 cm depth). Maintenance workload levels were determined by the same experienced National Hunt trainer; typical training sessions consisted of a warm up (walk and trot) to the gallop (1000 m) followed by a canter interval run: 0.38 km, after which horses walked 0.38 km back to the start; this process was then repeated a further two times. Mean HR, mean speed, and mean stride frequency (SF) for each run was recorded. Mean HR was used to calculate the mean percentage of HR maximum (%HRmax) for each horse between canter runs for individual training sessions and across the 6-week period. A series of one-way ANOVAs (significance: P < 0.05) with post hoc paired t-tests (Bonferroni-adjusted alpha: P < 0.01) examined if differences in %HRmean, mean speed, and mean SF occurred across the cohort and for individual horses. No significant differences in %HRmax, mean speed, or mean SF were found at the cohort or individual level (P > 0.05). The trainer rated all horses working at maintenance (aerobic) levels; however, descriptive analysis identified that 74%, 43%, and 2% of gallop runs exceeded the anaerobic threshold when set at 75%, 80%, and 85% of HRmax. The results provide evidence that HRM can provide trainers with a more accurate appraisal of racehorse workload compared to visual assessment during training. Increasing industry understanding of how HRM can be used to monitor fitness within training can enhance equine welfare by preparing horses appropriately for the demands of competition.